Perception and knowledge of veterinary practitioners in Metropolitan Lima on the use of phytocannabinoids for medicinal use in companion animals - Hurtado Henriquez, Amelia Mariel (2020)
The aim of this study was to determine the perception and knowledge of veterinary practitioners in Metropolitan Lima on the use of phytocannabinoids for medicinal use in companion animals. An anonymous and voluntary survey was carried out on professionals who worked in veterinary centres in various districts of Lima, obtaining 151 surveys. Among the respondents, 56.3% (85) were women, the average age was 33.0 years and the average professional practice time was 7.1 years. The 85.4% (129) had heard about phytocannabinoids and, of these, 74.8% (113) knew that they are used in veterinary medicine. The most recognized medicinal uses in humans and animals were as antiepileptic, analgesic, and palliative in cancer patients. Of the respondents, 79.5% (120) considered that they should be beneficial, 18.5% (28) had the answer “maybe” and 2% (3) did not consider them beneficial. According to the Chi square test, there was no association between knowledge and the demographic variables evaluated. The study shows that there is a favourable perception in the majority of veterinary professionals surveyed regarding the use of these cannabinoids in clinical practice, but knowledge about this is still incipient.